The Post-Modern Hero: When the Spectacle Becomes Reality (KULT_online, 2016)
In his darkly thought-provoking book, Franco ‘Bifo’ Berardi considers capitalism’s effect on mental health through the lens of crime and suicidal mass murder. Heroes speculates on the trajectory of human history by delineating the implications of the growth of spectacular suicidal mass murder: capitalism’s bleeding together of capital, politics, media, virtuality, mental health, and violence. For Berardi, suicide is a declaration of autonomy as well as a form of resistance that represents “the most significant political act” (195) in the current age of nihilism and capitalist absolutism. What is Berardi’s answer to capitalist absolutism and a regressive, violent future? Nothing is to be done, so don’t hope. Distance yourself with irony. While Heroes does not claim to be a manifesto, Berardi does intend it as an anecdote to the degeneration of human evolution and a map for a new ethics.